Фактори, які впливають на довголіття індивіда у обраному виді одноборства - Іващенко, О. О.; Самойленко, О. А.; Полякова, Оксана Олександрівна; Литвиненко, А. В.; Шепель, Є. В.; Грицай, В. В. (Національний педагогічний університет ім. М. П. Драгоманова, 2023)
Відповідно до результатів аналізу науково-методичної, спеціальної та довідкової літератури встановлено, що актуальним питанням визначення впливу вікових особливостей на спортивний результат одноборців в системі їхньої багаторічної підготовки – присвячено недостатню кількість наукових праць. Це підкреслює актуальність та практичну складову обраного напряму наукової розвідки. Головною метою дослідження є визначення провідних чинників (факторів), які забезпечують довголіття спортсменів та спортсменок у обраному виді одноборства (на прикладі боротьби самбо). Методи дослідження: абстрагування, аналіз, дедукція, індукція, моделювання, порівняння, синтез, формалізація (експертне оцінювання). В результаті теоретичного дослідження членами науково-дослідної групи визначені провідні чинники та фактори, які забезпечують довголіття спортсменів у обраному виді спортивної боротьби (на прикладі борців самбо, спортивний та бойовий розділи). Перспективи подальших досліджень у обраному напрямі наукової розвідки передбачають розроблення нормативної бази зі спеціальної фізичної підготовки для одноборців-ветеранів старших вікових груп (на прикладі борців самбо).

According to the Results of the Analysis of Scientific-Methodical literature, it was established that the actual issue of determining the influence of age characteristics on the Sports Performance of athletes who specialize in Martial Arts in the System of their long-term training is devoted to an insufficient number of Scientific works. This emphasizes the relevance and practical component of the chosen direction of Scientific Research. The research was carried out in accordance with the plan of the initiative scientific project «Longevity in Martial Arts-2023/2024. The main goal of the study is to determine the leading factors that ensure the longevity of athletes in the chosen type of Sports wrestling (using the example of athletes who specialize in Sambo wrestling). Research methods: abstraction, analysis, deduction, induction, modeling, comparison, synthesis, formalization (expert assessment). As a result of a theoretical study, the members of the scientific research group determined the leading factors and factors that ensure the longevity of athletes in the chosen type of sports wrestling (on the example of athletes who specialize in Sambo – sports and combat Sambo). The Results of the Research are implemented in the System of long-term training of sportsmen and women who specialize in sports of wrestling (full-contact Martial Arts) of the Dnipropetrovsk, Kyiv and Kharkiv regions. Prospects for further Research in the chosen field of Scientific Research include the development of a regulatory framework for Special Physical training for athletes of older age groups (veterans) who specialize in Sambo and Judo wrestling.
Determination of factors that affect the longevity of an individual in the chosen type of martial arts
Keywords: багаторічна підготовка; боротьба; ветеранський спорт; вікові особливості; довголіття; одноборці; психосоматичний стан; рухові навички; спортивна кваліфікація; стан здоров'я; фактори; фізичний розвиток; long-term training; wrestling; veteran sports; age characteristics; longevity; wrestlers (fighters); psychosomatic condition; motor skills; sports qualification; state of health; factors; physical development